Assessment of knowledge and disposal practices of unused and expired household medicines in a community in Liberia - Jerry Toe; Edidiong Orok; Patrick Erah (Elsevier, 2023)
Background: Expansion of pharmaceutical industries and improved availability of pharmaceuticals across the world have contributed to an increase in drug usage and accumulation in homes. Improper disposal of expired and unused medications has several consequences such as environmental pollution, and childhood poisoning. Objectives: The aim of the study was to assess the knowledge on disposal as well as disposal practices of unused and expired household medicines in the Parker Corner Road Community in Brewerville, Liberia. Methods: This study was a cross-sectional survey conducted among 162 residents of Parker Corner Road Community using face-to-face interviews. Outcomes measured were knowledge of disposal as well as disposal practices of unused and expired household medicines. The data collected were analysed using descriptive statistics. Results: Majority of respondents (55.6%) were female and 23.5% had university education. 71% of the respondents reported that they had not received any information on safe disposal practices while 64.2% admitted that they often did not read and follow disposal instructions. The most popular disposal practices were disposal of the drugs along with household waste (61.1%) and flushing them down the toilets or sinks (25.3%). Majority of the respondents (82.1%) were aware of the health effects arising from improper disposal of unused and expired medicines while 64.2% usually read medicine disposal instruction on the package. Only about 3% of them knew of expired medication take-back system and 33.3% knew nothing about medication expiration date. Conclusion: The study revealed insufficient knowledge as well as inappropriate disposal practices of unused and expired medicines among residents of Parker Corner Road Community in Brewerville. There is need to organize a public enlightenment programme on safe, appropriate use, as well as disposal of unused and expired medicines.